Neurotrophic Factors in Development and Regulation of Respiratory Control. Issue 3 (July 2013) - Ogier, Michael; Kron, Miriam; Katz, David M.
Abstract: Neurotrophic factors (NTFs) are a heterogeneous group of extracellular signaling molecules that play critical roles in the development, maintenance, modulation and plasticity of the central and peripheral nervous systems. A subset of these factors, including members of three multigene families—the neurotrophins, neuropoetic cytokines and the glial cell line‐derived neurotrophic factor ligands—are particularly important for development and regulation of neurons involved in respiratory control. Here, we review the functional biology of these NTFs and their receptors, as well as their roles in regulating survival, maturation, synaptic strength and plasticity in respiratory control pathways. In addition, we highlight recent progress in identifying the role of abnormal NTF signaling in the molecular pathogenesis of respiratory dysfunction in Rett syndrome and in the development of potential new NTF‐targeted therapeutic strategies. © 2013 American Physiological Society. Compr Physiol 3:1125‐1134, 2013.